Helicobacter pylori and cardiovascular risk: Only a dead Helicobacter is a good Helicobacter?. Issue 6 (31st August 2022) - Wernly, Sarah; Semmler, Georg; Völkerer, Andreas; Flamm, Maria; Aigner, Elmar; Niederseer, David; Wernly, Bernhard; Datz, Christian
Abstract: Objectives: Helicobacter pylori ( H. pylori ) and cardiovascular (CV) disease share common symptoms and underlie many general medical complaints. Preliminary studies suggest an association between H. pylori positivity and CV risk, and gastroenterological guidelines recommend eradication of H. pylori in patients with manifest atherosclerosis. Therefore, the aim of this study was to examine the reciprocal association of H. pylori positivity and CV risk for their independence of shared risk factors. Methods: We included 3284 asymptomatic participants of a colorectal cancer screening cohort who were offered and underwent upper gastrointestinal endoscopy. We calculated the 10‐year risk for a CV event using the novel SCORE2 for each patient. We evaluated the association between H. pylori positivity and CV risk assessed by SCORE2 using both multilevel logistic and linear regression. We adjusted for age, sex and the concomitant diagnosis of metabolic syndrome. Lastly, we assessed the association between H. pylori status and mortality using proportional hazard Cox regression. Results: In total, 2659 patients were H. pylori negative and 625 H. pylori positive. Helicobacter pylori positivity was associated with SCORE2 and remained so ( r  = .33; 95% CI 0.09–0.57; p  = .006) after adjustment for age, sex, and the diagnosis of metabolic syndrome. Also, SCORE2 was associated with higher odds for H. pylori positivity (aOR 1.03 95% CI 1.01–1.05; p  = .02) even after multivariable adjustment. Helicobacter pylori positivity was associated with neither CV (HR 0.60 95% CI 0.14–2.63; p  = .50) nor all‐cause (HR 1.20 95% CI 0.77–1.87; p  = .43) mortality during a median follow‐up of 9 years. Conclusions: In our study, H. pylori positivity and CV risk were independently associated. This did not translate into a dissimilar CV mortality between H. pylori positive and H. pylori negative patients. However, the overwhelming majority of our patients underwent H. pylori eradication. We, therefore, think that H. pylori eradication is at least safe from a cardiovascular perspective and warranted from gastrointestinal standpoint.